The Training Implementation and Effectiveness Among Majlis Daerah Cameron Highlands Employees: From the Perspective of Human Capital Management - Adnan, Nor Izzati Azlin; Low, Kah Choon; Chong, Say Lee (2024)
The purpose of this study was to explore the implementation and effectiveness of training provided by the Cameron Highlands District Council (MDCH) in meeting the needs and functions of the department’s employees. Through this study, the researcher revealed that the work performance problems faced by MDCH’s employees called for the need for more training for them. A qualitative interview approach was used, and primary data was collected from 15 informants positioned in various departments in the MDCH. Through this study, the researcher found how the training was set for each employee in the MDCH. The findings of this study showed that work performance problems and training effectiveness have a significant relationship. The work performance problems experienced by MDCH employees were caused by the lack of acceptance of specific forms of training in their own field of work. The results of this study will help the management of the MDCH in improving the problems or needs required by the employees at the MDCH. Indirectly, this study can also help in diversifying the form of specialized training according to the scope of tasks and work areas available at MDCH